2020
DOI: 10.3758/s13428-020-01420-5
|View full text |Cite
|
Sign up to set email alerts
|

Piecewise latent growth models: beyond modeling linear-linear processes

Abstract: Piecewise latent growth models (LGMs) for linear-linear processes have been well-documented and studied in recent years. However, in the latent growth modeling literature, advancements to other functional forms as well as to multiple changepoints or knots have been nearly non-existent. This manuscript deals with three extensions. The first is to a piecewise latent growth model incorporating higher-order polynomials. The second is to extend the basic framework to three phases. The last extension is to inherentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…Consequently, an alternative so-called the linear piecewise model was tested. Linear piecewise models are used for modeling changes that deviate from a simple linear trajectory; when the rate of change during the specific time window differs from the rate of change during another time window ( 54 ). The simplest variant of the linear piecewise model is the two-phase model with two linear slopes and a single change point ( 55 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, an alternative so-called the linear piecewise model was tested. Linear piecewise models are used for modeling changes that deviate from a simple linear trajectory; when the rate of change during the specific time window differs from the rate of change during another time window ( 54 ). The simplest variant of the linear piecewise model is the two-phase model with two linear slopes and a single change point ( 55 ).…”
Section: Resultsmentioning
confidence: 99%
“…In this model, the first linear slope represents the changes that occur during the first phase of the study, and the second linear slope describes the trajectories during the second phase. The change point represents the fixed time point where these two linear slopes are to be joined ( 54 ). Based on the plot (see Figure 1 ; clinical scale), the change point was assumed to be at T3, and therefore the unconditional two-phase linear piecewise model was tested.…”
Section: Resultsmentioning
confidence: 99%
“…Second, the linear-linear piecewise functional form can be utilized to approximate nonlinear change patterns in a variety of situations in practice, for example, earlier and later development stages in psychology, treatment and follow-up phases in psychotherapy, and adolescent and adulthood periods in behavioral science. It could be extended further to analyze a phenomenon with three stages and estimate fixed knots (Harring et al, 2021). Thus, the proposed model can also be extended for joint development in cases where three phases are scientifically justified.…”
Section: Methodological Considerations and Future Directionsmentioning
confidence: 99%
“…Multiple parametric functional forms, such as polynomial, exponential, logistic, and Jenss-Bayley growth curves, have been proposed to capture characteristics of nonlinear change patterns. Earlier studies, for example, Harring et al (2006); Flora (2008); Dumenci et al (2019); Kohli (2011); ; ; Kohli et al (2015a,b); Liu and Perera (2021); Harring et al (2021) have also proposed and employed several piecewise models (i.e., the growth curve model with semi-parametric functions), such as linear-linear piecewise, linear-quadratic piecewise, and piecewise functions with three segments, to describe nonlinear curves which have different change rates to different stages in longitudinal processes. These studies have also demonstrated that the piecewise functions are versatile and valuable in modeling repeated outcomes in multiple domains, including developmental, cognitive, and biomedical.…”
Section: Traditional Latent Basis Growth Modelmentioning
confidence: 96%